Review of Hooke and Jeeves Direct Search Solution M ethod Analysis Applicable To Mechanical Design Engineering - Mr. G.S KIRGAT; Prof. A.N Surde (International Journal of Innovations in Engineering Research and Technology, 2021)
Role of optimization in engineering design is prominent one with the a dvent of computers. Optimization has become a part of computer aided design methodology. It is primarily being used in those design activities in which the goal is not only to achieve a feasible design, but als o a design objective. The paper reviews the optimization in detail followed by the literature review and b rief discussion of Hooks and Jeeves Method Analysis with an example.